Thanatophoric Dysplasia - Basyir, Vaulinne; Yusrawati, Yusrawati; Khatimah, Gistin Husnul (Andalas Obstetrics And Gynecology Journal, 2021)
Background: The term tanatophorik comes from the Greek word thanatophorus which means "innate death" or "bearing death". The problem that underlies this disease is the process of bone formation. This disease is associated with an autosomal dominant inherited mutation of the fibroblast growth factor 3 receptor (FGFR3) gene on the arm of chromosome 4 (4p16.3). Because FGFR3 is the main modulator in bone formation, the typical clinical features of this disease include shortening of the extremities, curved femur, clover-like skull and narrowing of the thoracic cavity.Tanatophoric dysplasia is a skeletal disorder that is "lethal" or deadly. The deaths occurred due to respiratory failure caused by reduced chest cavity capacity, hypoplastic lungs and / or brainstem compression.Destination: Reported a case of thanatophoric dysplasiaMethod: Case Report Case Report: Case 33 years old woman, with preterm parturient G1P0A0H0 35-36 weeks 1 latent phase + history of 2x laparotomy + suspected fetal tanatophoric dysplasia. On ultrasound examination, it was found that BPD = 9.14 cm; AC = 30.56 cm; HC = 32.05 cm; FL = 2.55 cm; AFI; 9.06cm; SDAU = 1.72 cm. The presence of frontal bosing, saddle nose and micromilia (proximal, distal, phalanges) was found. The patient was planned for vaginal delivery and the progress of labor was followed. Patients provided informed consent regarding the possibility of fetal death during labor and after birth. During the active phase of the labor process, hypotony uterine innersia occurs and oxytocin drip is performed to accelerate labor. The baby was born male, weight 2175 grams, body length 34 cm and A / S: 1/0. Postmortem physical examination revealed macroscopic findings of tanatophoric dysplasia infants such as hypertelorism, low nasal bridge, cranio-facial disproportion. Narrow chest with protruding abdomen and short, bent limbs.Conclusion: Tanatophoric dysplasia is "lethal" skeletal dysplasia. Careful prenatal examination is required in diagnosis and termination of pregnancy. Keywords: Thanatophoric dysplasia, prenatal diagnosis